Shattered Nerves: Echoes of Greek Identity Resonating Through the Idiom of Nevra - Xenocostas, Spyridoula (Culture, 1993)
This article examines narratives on nevra as told by first generation Greek women in Montreal. It explores nevra as an active expression and transformation of Greek ethnic identity. As an expressive form, nevra gives voice to various cultural, social and economic pressures within the Greek immigrant context. At the same time, however, in acting as a mechanism of social adjustment to the complex and contradictory forces that impact the individual, the experience of nevra assumes a transformative role in the manner in which ethnic and gender related identities are perceived and lived. In consciously manipulating the idiom of nevra Greek immigrant women can critically reflect and modify the sources of their oppression. This form of "resistance" however, in the absence of any concrete empowerment strategies, does not permit them to overcome overwhelming social forces imposed by family, community and society, and does not significantïy transform constraints of both culture and gender.